Menilik Efektivitas Penegakan Hukum Batas Usia Minimal Kawin dan Kebijakan Negara - Puspaningtyas Panglipurjati (Kertha Wicaksana, 2025)
Law Number 16 of 2019, concerning Amendments to Law Number 1 of 1974 concerning Marriage, changes the minimum age limit for marriage to 19 years for men and women as an effort to suppress and eliminate the practice of child marriage in Indonesia. In addition to changing the minimum age limit for marriage, the law also opens up the opportunity to apply for a dispensation to marry for those not yet 19. Several data collected show that the number of child marriages and marriage dispensations in Indonesia still tends to be high, and there is still inconsistency among judges in examining applications for marriage dispensations based on the Supreme Court Regulation concerning Guidelines for Adjudicating Applications for Marriage Dispensations. Therefore, this study aims to capture the conditions of child marriage and marriage dispensations in Indonesia, especially after the revision of the minimum age limit for marriage, as well as the effectiveness of law enforcement. The method used in this study is the normative legal research method, which traces primary legal materials and secondary legal materials, such as reports and journals related to child marriage. Based on the research conducted, several recommendations are given, including taking preventive measures against several main factors in the occurrence of child marriage, especially in provinces that are based on data including provinces with the highest percentage of child marriage, one of which is by recommending the local government to form regional regulations to prevent and overcome child marriage.